Processo de avaliação dos planos municipais de saneamento básico de municípios do noroeste Rio-Grandense - Silva, Tainara Casa Nova (2022)
One of the challenges faced by small municipalities is the implementation of public policies in order to solve problems related to basic sanitation. In this context, the Municipal Basic Sanitation Plan is mandatory provided for in Federal Law 11.445/2007, so it is of paramount importance for plans to be prepared in accordance with the local reality. This study aims to identify and analyze the PMSB of the 27 municipalities in Northwest Rio Grande. The research was carried out in an exploratory way, with a qualitative approach, in order to provide greater familiarity with the problem, with a view to making it more explicit. The methodology was divided into three stages: a reference research and a documental research, with reading of the Municipal Basic Sanitation Plans (stage 1), through the application of a simplified questionnaire with the municipal responsible for the respective documents (stage 2) and technical evaluation of the PMSB, through a methodology adapted from the Ministry of Cities roadmap (step 3), aiming to evaluate the compliance of plans according to minimum content, provided for in Law Nº. 11.445/2007 and in Law Nº. 14.026/2020. Among the difficulties faced are: not having the document digitally; claiming that the PMSB does not exist and confusing it with the PGRS. The 27 municipalities responded to the simplified questionnaire and, in general, it was observed that although those responsible had participated in the committees, the information was not always clear, which indicates that there was probably little active participation of the holder in the elaboration of the plan. With the tool adapted from the Ministry of Cities roadmap (2016), it was possible to evaluate 23 municipalities, reaching as a final conclusion that 12 municipalities (52.17%), the Plan satisfactorily contemplated minimum content; 5 municipalities (21.74%), the Plan contemplated the content in a moderate way, it was recommended to anticipate the revision of the document; and 6 municipalities (26.10%), the Plan contemplated a small part of the minimum content, it was recommended to immediately review the document. As for the tool used, it was of paramount importance to obtain the overall result, it is recommended to use it as a primary instrument serving as a basis for performing other detailed analyzes regarding the quality of content in the PMSB. The use of the methodology adapted from the Ministry of Cities (2016), named in this study as an analytical tool for simplified analysis of the minimum content of the PMSB, which exclusively identifies the existence of the minimum content, but does not explore the results obtained by each municipality. In this sense, it is essential that new research be directed towards measuring the performance of actions carried out in the long term, adopting qualitative and quantitative indicators for this comparison.